Advantages and Challenges of Inclusive Education: Analysis of Teachers’ Subjective Experiences - Tomėnienė, Laima; Alifanovienė, Daiva (Social Welfare: Interdisciplinary Approach, 2023)
The article aims to reveal the context of the expression of advantages and challenges of inclusive education. The research was based on an interpretive approach to research methodology in order to find out the attitude of the research participants – teachers of general education schools – about the reality of the implementation of inclusive education in the context of general education. In order to achieve high-quality education for all, the teachers saw the positive benefits of inclusion for all participants in the process of education, the community of the institution, the positive process of socialization, and the emotional well-being of children. It is emphasized that the successful implementation of the principle of inclusion in the school is impossible without changing values, attitudes, and beliefs, constructive and effective cooperation, team work of teachers and educational support specialists both when planning activities and directly working in the classroom.
Keywords: inclusive education; challenges; teachers; experiences